Electrophotographic photoreceptor, process cartridge, electrophotographic device, and method of manufacturing electrophotographic photoreceptor
Patent Information
- Application Number
- JP2022020583
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-02-14
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2042-02-14
AI Technical Summary
Existing electrophotographic photoreceptors face issues with non-uniform dispersion of fluorine atom-containing resin particles in the surface layer, leading to significant potential fluctuations during repeated use, which affect image quality and durability.
The use of a polymer A with a specific structural unit, represented by formula (1), as a dispersant for fluorine atom-containing resin particles in the surface layer, enhances uniform dispersion and suppresses potential fluctuations by minimizing charge accumulation on the -(CF2)n- chain.
The solution achieves uniform dispersion of fluorine atom-containing resin particles, reducing potential fluctuations and improving the mechanical durability and image quality of electrophotographic photoreceptors during repeated use.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to an electrophotographic photoreceptor, a process cartridge having the electrophotographic photoreceptor, an electrophotographic apparatus having the electrophotographic photoreceptor, and a method for manufacturing an electrophotographic photoreceptor. [Background technology]
[0002] Electrophotographic photoreceptors containing organic photoconductive materials (charge-generating materials) are widely used in electrophotographic devices. In recent years, there has been a demand for improved mechanical durability (wear resistance) of electrophotographic photoreceptors in order to extend their lifespan and improve image quality during repeated use.
[0003] One technique for improving the wear resistance of electrophotographic photoreceptors is to incorporate fluorine atom-containing resin particles into the surface layer of the electrophotographic photoreceptor, thereby reducing the frictional force between the surface layer and components that come into contact with the surface of the electrophotographic photoreceptor, such as cleaning blades. Patent Document 1 discloses a technique for forming a surface layer using a dispersion of fluorine atom-containing resin particles, such as polytetrafluoroethylene resin particles, as a coating liquid for the surface layer.
[0004] Furthermore, when preparing a dispersion of fluorine atom-containing resin particles, a method is known in which a fluorine atom-containing (meth)acrylic polymer is used as a dispersant to improve the dispersibility of the fluorine atom-containing resin particles. Patent documents 2 to 4 disclose a technique for improving the dispersibility of fluorine atom-containing resin particles by using a fluorine atom-containing (meth)acrylic polymer having a specific structure as a dispersant. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 06-332219 [Patent Document 2] Japanese Patent Publication No. 2012-189715 [Patent Document 3] Japanese Patent Publication No. 2009-104145 [Patent Document 4] Japanese Patent Publication No. 2021-47236 [Overview of the project] [Problems that the invention aims to solve]
[0006] However, while the technologies disclosed in Patent Documents 2 to 4 yield electrophotographic photoreceptors with excellent uniformity of fluorine atom-containing resin particle dispersion in the surface layer, there were cases where potential fluctuations could not be sufficiently suppressed during repeated use of the electrophotographic photoreceptor. In other words, there was room for improvement in suppressing potential fluctuations during repeated use of the electrophotographic photoreceptor in the technologies disclosed in Patent Documents 2 to 4.
[0007] One aspect of this disclosure aims to provide an electrophotographic photoreceptor that exhibits excellent uniformity in the dispersion of fluorine atom-containing resin particles in the surface layer and suppresses potential fluctuations during repeated use. Another aspect of this disclosure relates to a process cartridge equipped with the electrophotographic photoreceptor, and an electrophotographic apparatus equipped with the process cartridge. Another aspect of this disclosure relates to a method for manufacturing the electrophotographic photoreceptor described above. [Means for solving the problem]
[0008] An electrophotographic photoreceptor according to one aspect of the present disclosure is an electrophotographic photoreceptor having a surface layer, characterized in that the surface layer contains fluorine atom-containing resin particles, a binder material, and a polymer A having a structural unit represented by the following formula (1). [ka] (In formula (1), R 11 This represents a hydrogen atom or a methyl group. R 12 This represents a single bond, a methylene group, or an ethylene group. n is an integer greater than or equal to 3. n reduction Rf 1 Each of them operates independently. A perfluoroalkylene group having 1 to 5 carbon atoms, or It exhibits a perfluoroalkylidene group having 1 to 5 carbon atoms, Rf 2 This represents a perfluoroalkyl group with 1 to 5 carbon atoms.
[0009] Furthermore, process cartridges according to other embodiments of the present disclosure are characterized in that they integrally support the electrophotographic photoreceptor and at least one means selected from the group consisting of a charging means, a developing means, and a cleaning means, and are detachably attached to the electrophotographic apparatus body.
[0010] Furthermore, an electrophotographic apparatus according to another aspect of the present disclosure is characterized by comprising the electrophotographic photoreceptor, as well as a charging means, an exposure means, a developing means, and a transfer means.
[0011] Furthermore, a method for manufacturing an electrophotographic photoreceptor according to another aspect of the present disclosure is a method for manufacturing an electrophotographic photoreceptor having a surface layer, characterized by comprising the steps of: preparing a coating solution for a surface layer containing a polymer A having a structural unit represented by the following formula (1), fluorine atom-containing resin particles, and at least one selected from a binder and a raw material for a binder; and forming a coating film of the coating solution for a surface layer, and forming the surface layer by performing at least one treatment selected from drying and curing on the coating film. [ka] (In formula (1), R 11 This represents a hydrogen atom or a methyl group. R 12 This represents a single bond, a methylene group, or an ethylene group. n is an integer greater than or equal to 3. n reduction Rf 1 Each of them operates independently. A perfluoroalkylene group having 1 to 5 carbon atoms, or represents a perfluoroalkylidene group having 1 to 5 carbon atoms, Rf 2 represents a perfluoroalkyl group having 1 to 5 carbon atoms.)
Advantages of the Invention
[0012] According to one aspect of the present disclosure, there is provided an electrophotographic photoreceptor excellent in the uniformity of dispersion of fluorine atom-containing resin particles in the surface layer and having suppressed potential fluctuations during repeated use.
Brief Description of the Drawings
[0013] [Figure 1] It is a schematic diagram showing an example of the configuration of the electrophotographic photoreceptor of the present disclosure. [Figure 2] It is a diagram showing an example of a polishing machine using a polishing sheet. [Figure 3] It is a schematic diagram showing an example of a process cartridge having an electrophotographic photoreceptor. [Figure 4] It is a schematic diagram showing an example of an electrophotographic apparatus having an electrophotographic photoreceptor.
Modes for Carrying Out the Invention
[0014] The electrophotographic photoreceptor according to the present disclosure is an electrophotographic photoreceptor having a surface layer, wherein the surface layer contains fluorine atom-containing resin particles, a binder material, and a polymer A having a structural unit represented by the following formula (1).
Chemical formula
[0015] As a result of our investigations, we have found that by using the electrophotographic photoreceptor according to the present disclosure described above, it is possible to achieve excellent uniformity in the dispersion of fluorine atom-containing resin particles in the surface layer, and to suppress potential fluctuations during repeated use.
[0016] Here, the inventors believe that polymer A having the structural unit shown in formula (1) above acts as a dispersant for fluorine atom-containing resin particles in the process of preparing a coating solution for the surface layer of an electrophotographic photoreceptor.
[0017] The inventors speculate that the electrophotographic photoreceptor according to this disclosure exhibits excellent uniformity in the dispersion of fluorine atom-containing resin particles in the surface layer and excellent suppression of potential fluctuations during repeated use, as follows.
[0018] Fluorine atom-containing resin particles and -(CF2) n Electrophotographic photoreceptors having a surface layer containing a chain-containing dispersant tend to exhibit large potential fluctuations during repeated use. The following are possible reasons for this:
[0019] In the surface layer, fluorine atom-containing resin particles are affected by the dispersant's -(CF2) n -It is attached to the chain. These fluorine atom-containing resin particles are attached to it - (CF2) n -Charge is thought to easily accumulate in the chain. Therefore, fluorine atom-containing resin particles and -(CF2) n -When an electrophotographic photoreceptor having a surface layer containing a chain-containing dispersant is used repeatedly, fluorine atom-containing resin particles adhere to it.-(CF2) n -Charge accumulates in the chain. This is thought to cause large potential fluctuations.
[0020] Based on the inventors' investigations, -(CF2) n -When incorporating a dispersant having a chain into the surface layer, -(CF2) n We discovered that interposing oxygen atoms within the chain suppresses the accumulation of charge. We also found that the more carbon atoms in a continuous chain of -(CF2)- without interposing oxygen atoms there are, the more easily charge accumulates and the greater the potential fluctuation tends to be.
[0021] Therefore, as a result of further investigation, the inventors of this invention concluded that -(CF2) n - We found that by using polymer A having the structural unit shown in formula (1) above as a chain-containing dispersant, charge accumulation can be suppressed, and potential fluctuations during repeated use can be suppressed.
[0022] Rf in equation (1) above 1 Rf is a perfluoroalkylene group or a perfluoroalkylidene group having 5 or fewer carbon atoms, 2 This is a perfluoroalkyl group having 5 or fewer carbon atoms. That is, in the structural unit shown in formula (1) above, the number of carbon atoms in the continuous -(CF2)- chain without an intervening oxygen atom is 5 or less. This is thought to suppress the accumulation of charge in the structural unit shown in formula (1) above.
[0023] In equation (1) above, n Rf 1 Each of these is independently a perfluoroalkylene group having 1 to 3 carbon atoms, or a perfluoroalkylidene group having 1 to 3 carbon atoms, and Rf 2 It is more preferable that the element is a perfluoroalkyl group having 1 to 3 carbon atoms.
[0024] In equation (1) above, n Rf 1 , and Rf 2 The total number of carbon atoms is preferably 6 or more and 9 or less, from the viewpoint of improving the uniformity of the dispersion of fluorine atom-containing resin particles and suppressing potential fluctuations.
[0025] Also, R in equation (1) above 12The fact that R is a single bond, a methylene group, or an ethylene group reduces the surface energy difference between the structural unit shown in formula (1) and the fluorine atom-containing resin particles. Therefore, the fluorine atom-containing resin particles adhere more easily to the structural unit shown in formula (1), and it is thought that the uniformity of the dispersion of fluorine atom-containing resin particles in the surface layer can be sufficiently high. 12 It is preferable that it is a methylene group.
[0026] In this disclosure, the structural unit represented by formula (1) above includes the structures shown in Tables 1 and 2. In Tables 1 and 2, multiple Rf 1 This is the Rf at the end of the main chain of polymer A mentioned above. 2 (Farthest from) Rf 1-1 , Rf 1-2 , Rf 1-3 , Rf 1-4 , and Rf 1-5 As shown.
[0027] [Table 1]
[0028] [Table 2]
[0029] In the polymer A described above, the composition ratio of the structural units represented by formula (1) is preferably 5% to 95% of the total number of structural units constituting polymer A, from the viewpoint of improving the uniformity of the dispersion of fluorine atom-containing resin particles in the surface layer. Furthermore, in the polymer A described above, the composition ratio of the structural units represented by formula (1) is more preferably 50% to 95% of the total number of structural units constituting polymer A, and even more preferably 70% to 90% of the total number of structural units constituting polymer A.
[0030] Furthermore, in polymer A, the composition ratio of the structural units represented by formula (1) is preferably 0.1% by mass or more and 80% by mass or less relative to the total mass of the structural units constituting polymer A, from the viewpoint of improving the uniformity of the dispersion of fluorine atom-containing resin particles in the surface layer. Moreover, in polymer A, the composition ratio of the structural units represented by formula (1) is more preferably 1% by mass or more and 80% by mass or less relative to the mass of the structural units constituting polymer A, and even more preferably 4% by mass or more and 66% by mass or less.
[0031] The polymer A preferably further has structural units represented by the following formula (2). [ka] (In formula (2), Y A1 This shows an unsubstituted alkylene group, Y B This represents an unsubstituted alkylene group, a halogen-substituted alkylene group, a hydroxyl-substituted alkylene group, an ester bond (-COO-), an amide bond (-NHCO-), or a urethane bond (-NHCOO-), or a divalent linking group that can be derived by combining one or more of these groups and bonds with -O- or -S-, or a single bond. Z A This represents the structure shown in formula (2A), a cyano group, or a phenyl group. R 21 , and R 22 These each independently represent either a hydrogen atom or a methyl group. m is an integer between 25 and 150 (inclusive). [ka] (In formula (2A), Z A1 This represents an alkyl group having 1 to 4 carbon atoms.
[0032] In formula (2), Y B If it shows an ester bond, -Y A1 -Y B -CH2- is -YA1 -CO-O-CH2- and -Y A1 Either -O-CO-CH2- is acceptable, preferably -Y A1 It is -CO-O-CH2-. Also, in equation (2), Y B If it shows an amide bond, -Y A1 -Y B -CH2- is -Y A1 -NH-CO-CH2- and -Y A1 Either -CO-NH-CH2- is acceptable, preferably -Y A1 It is -NH-CO-CH2-. Also, in equation (2), Y B If it is a urethane bond, -Y A1 -Y B -CH2- is -Y A1 -NH-CO-O-CH2- and -Y A1 Either -O-CO-NH-CH2- is acceptable, preferably -Y A1 It is -NH-CO-O-CH2-.
[0033] Preferably, the polymer A described above has only the structural unit represented by formula (1) and the structural unit represented by formula (2) as structural units.
[0034] In equation (2) above, -Y A1 -Y B -but, -Y A1 -(Y A2 ) b -(Y A3 ) c -(Y A4 ) d -(Y A5 ) e -(Y A6 ) f -The structure shown is preferable. Here, Y A1 This shows an unsubstituted alkylene group, Y A2 This represents a methylene group substituted with at least one selected from the group consisting of hydroxyl groups and halogen atoms, Y A3 This shows an unsubstituted alkylene group, Y A4 Y represents an ester bond, amide bond, or urethane bond. A5This shows an unsubstituted alkylene group, Y A6 represents an oxygen atom or a sulfur atom, and b, c, d, e, and f are each independently 0 or 1.
[0035] Examples of structural units represented by formula (2) above include the structures shown in Tables 3-1 and 3-2. [Table 3-1] [Table 3-2]
[0036] In polymer A, the ratio of the structural units represented by formula (1) to the structural units represented by formula (2) and their content, and the ratio of the content of the structural units represented by formula (1) to the content of the structural units represented by formula (2), is preferably 1:19 to 19:1 in molar ratio. Furthermore, in polymer A, the ratio of the structural units represented by formula (1) to the structural units represented by formula (2) and their content is more preferably 1:1 to 19:1 in molar ratio, and even more preferably 7:3 to 9:1 in molar ratio.
[0037] The weight-average molecular weight of polymer A is preferably 16,000 to 100,000, from the viewpoint of improving the uniformity of the dispersion of fluorine atom-containing resin particles in the surface layer and suppressing potential fluctuations. Furthermore, the weight-average molecular weight of polymer A is more preferably 18,000 to 80,000.
[0038] The weight-average molecular weight of polymer A can be measured and calculated by the following method. (Weight-average molecular weight measurement by GPC) The weight-average molecular weight can be measured by gel permeation chromatography (GPC) as follows: First, the sample is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. Then, the resulting solution is filtered through a solvent-resistant membrane filter, "Maeshori Disc" (manufactured by Tosoh Corporation), with a pore diameter of 0.2 μm, to obtain the sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is approximately 0.8% by mass. This sample solution is then used for measurement under the following conditions. • Equipment: HLC8120 GPC (Detector: RI) (Manufactured by Tosoh Corporation) • Columns: Shodex KF-801, 802, 803, 804, 805, 806, 807 (7 columns, manufactured by Showa Denko) • Eluent: Tetrahydrofuran (THF) ·Flow rate: 1.0ml / min Oven temperature: 40.0℃ • Sample injection volume: 0.10 ml For calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resin is used. Examples of standard polystyrene resins include the product names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500" (manufactured by Tosoh Corporation).
[0039] The content of polymer A in the surface layer is preferably 2% by mass or more and 10% by mass or less relative to the content of fluorine atom-containing resin particles in the surface layer, from the viewpoint of improving the uniformity of the dispersion of fluorine atom-containing resin particles in the surface layer and suppressing potential fluctuations. Furthermore, the content of polymer A in the surface layer is more preferably 4% by mass or more and 8% by mass or less relative to the content of fluorine atom-containing resin particles in the surface layer.
[0040] <Fluorine atom-containing resin particles> The surface layer of the electrophotographic photoreceptor relating to this disclosure contains fluorine atom-containing resin particles. The content of fluorine atom-containing resin particles in the surface layer is preferably 5% by mass or more and 40% by mass or less, relative to the total mass of the surface layer.
[0041] Examples of resins that may be contained in fluorine atom-containing resin particles include: polytetrafluoroethylene resin, polychlorotrifluoroethylene resin, polytetrafluoroethylene propylene resin, polyvinyl fluoride resin, polyvinylidene fluoride resin, or polydichlorodifluoroethylene resin. Furthermore, the fluorine atom-containing resin particles may contain multiple types of resins selected from those listed above. In addition, the fluorine atom-containing resin particles may be used individually or in combination of two or more types.
[0042] From the viewpoint of improving the uniformity of dispersion in the surface layer, the fluorine atom-containing resin particles are preferably polytetrafluoroethylene resin particles.
[0043] The arithmetic mean of the major axis of the primary particles of the fluorine atom-containing resin particles (average primary particle size) is preferably 150 nm to 300 nm from the viewpoint of improving the uniformity of dispersion within the surface layer and suppressing potential fluctuations. More preferably, the average primary particle size of the fluorine atom-containing resin particles is 180 nm to 250 nm. Here, the average primary particle size of the fluorine atom-containing resin particles is a value obtained by measuring from a secondary electron image acquired by observing a cross-section of the surface layer with a scanning electron microscope.
[0044] The average value of the roundness of the fluorine atom-containing resin particles (average roundness) is preferably 0.75 or higher. Here, roundness is a value calculated from the area and circumference measured for the primary particles of the fluorine atom-containing resin particles in the secondary electron image obtained by observing the cross-section of the surface layer with a scanning electron microscope.
[0045] The average primary particle size and average roundness of the fluorine atom-containing resin particles can be measured and calculated by the following method. (Measurement method for average primary particle size and average roundness) The average particle size and average roundness of fluorine atom-containing resin particles can be measured using a field emission scanning electron microscope (FE-SEM) as follows. First, fluorine atom-containing resin particles are attached to a commercially available carbon conductive tape, and any fluorine atom-containing resin particles not attached to the conductive tape are removed using compressed air. Then, platinum deposition is performed. Subsequently, the deposited fluorine atom-containing resin particles are observed using a Hitachi High-Technologies Corporation FE-SEM (S-4700). The measurement conditions for the FE-SEM are as follows. Acceleration voltage: 2kV WD: 5mm Magnification: 20,000 times Pixel count: 1280 pixels vertically, 960 pixels horizontally (size of each pixel: 5nm) Using ImageJ (open-source software from the National Institutes of Health (NIH)) to obtain the images, the Ferret diameter of 100 particles is determined, and the average value is calculated to determine the average particle size. Similarly, the area and perimeter are determined, the roundness is calculated using the following formula (II), the average value is calculated, and this is taken as the average roundness. Roundness = 4 × π × (area) ÷ (perimeter squared) Equation (II)
[0046] <Electrophotographic photoconductor> Figure 1 shows an example of the layer structure of an electrophotographic photoreceptor according to this disclosure. In the electrophotographic photoreceptor shown in Figure 1, an undercoat layer 102, a charge generation layer 103, a charge transport layer 104, and a surface layer 105 are laminated on a support 101. The photosensitive layer of the electrophotographic photoreceptor may be composed of a laminated photosensitive layer having a charge generation layer 103 and a charge transport layer 104 as shown in Figure 1, or it may be composed of a single-layer photosensitive layer containing both a charge generation material and a charge transport material.
[0047] The surface layer of the electrophotographic photoreceptor according to this disclosure contains fluorine atom-containing resin particles, a binder material, and polymer A having a structural unit represented by formula (1) above.
[0048] A method for manufacturing an electrophotographic photoreceptor according to this disclosure includes preparing coating solutions for each layer described later, applying the coating solutions for the desired layers in order, and drying them. In particular, the method for manufacturing an electrophotographic photoreceptor according to this disclosure is a method for manufacturing an electrophotographic photoreceptor having a surface layer, and comprises the following two steps: One is the step of preparing a coating solution for a surface layer containing a polymer A having a structural unit represented by formula (1) above, fluorine atom-containing resin particles, and at least one selected from a binder material and a raw material for a binder material. The other is the step of forming a coating film of the coating solution for the surface layer and forming the surface layer by performing at least one treatment selected from drying and curing on the coating film.
[0049] Methods for applying the coating solution include immersion coating, spray coating, inkjet coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, and ring coating. Among these, immersion coating is preferred from the viewpoint of efficiency and productivity.
[0050] The following describes the configuration of the electrophotographic photoreceptor related to this disclosure. <Support> The support for the electrophotographic photoreceptor is preferably conductive (a conductive support). The support can take various shapes, such as cylindrical, belt-shaped, or sheet-shaped. A cylindrical support is preferred. The surface of the support may also be subjected to electrochemical treatments such as anodizing, blasting, or cutting. Suitable materials for the support include metal, resin, and glass. Examples of metals include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof. Among these, an aluminum support made of aluminum is preferred. Furthermore, it is preferable to impart conductivity to resins and glass by processing them, such as by mixing or coating them with conductive materials.
[0051] <Conductive layer> A conductive layer may be provided on the support. By providing a conductive layer, scratches and irregularities on the surface of the support can be concealed, and light reflection on the surface of the support can be controlled. The conductive layer preferably contains conductive particles and a resin.
[0052] Examples of materials for conductive particles include metal oxides, metals, and carbon black. Examples of metal oxides include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, strontium titanate, magnesium oxide, antimony oxide, and bismuth oxide. Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, and silver. Among these, it is preferable to use metal oxide particles as conductive particles, and it is more preferable to use titanium oxide particles, tin oxide particles, or zinc oxide particles. When using metal oxide particles as conductive particles, the surface of the metal oxide particles may be treated with a silane coupling agent or the like, or the metal oxide particles may be doped with elements such as phosphorus or aluminum, or their oxides. Furthermore, the conductive particles may have a laminated structure comprising core material particles and a coating layer covering those particles. Examples of core material particles include titanium oxide particles, barium sulfate particles, and zinc oxide particles. Examples of coating layer particles include metal oxide particles such as tin oxide. Furthermore, when metal oxide particles are used as conductive particles, their volume-average particle size is preferably 1 nm or more and 500 nm or less, and more preferably 3 nm or more and 400 nm or less.
[0053] Examples of resins include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenolic resin, and alkyd resin. Furthermore, the conductive layer may further contain silicone oil, resin particles, a concealing agent such as titanium dioxide, etc.
[0054] A conductive layer can be formed by preparing a coating solution for a conductive layer containing the above-mentioned materials and solvents, forming this coating film on a support, and drying it. Examples of solvents used in the coating solution for a conductive layer include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Methods for dispersing conductive particles in the coating solution for a conductive layer include using a paint shaker, sand mill, ball mill, or liquid impaction type high-speed disperser.
[0055] The thickness of the conductive layer is preferably 1 μm or more and 50 μm or less, and particularly preferably 3 μm or more and 40 μm or less.
[0056] <Underlayer> In this disclosure, an undercoat layer may be provided on the support or conductive layer. Providing an undercoat layer enhances the interlayer adhesion function and imparts a charge injection blocking function.
[0057] The undercoat layer preferably contains a resin. Alternatively, the undercoat layer may be formed as a cured film by polymerizing a composition containing a monomer having polymerizable functional groups. Examples of resins include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, epoxy resin, melamine resin, polyurethane resin, phenolic resin, polyvinylphenol resin, alkyd resin, polyvinyl alcohol resin, polyethylene oxide resin, polypropylene oxide resin, polyamide resin, polyamic acid resin, polyimide resin, polyamide-imide resin, and cellulose resin. Examples of polymerizable functional groups found in monomers having polymerizable functional groups include isocyanate groups, blocked isocyanate groups, methylol groups, alkylated methylol groups, epoxy groups, metal alkoxide groups, hydroxyl groups, amino groups, carboxyl groups, thiol groups, carboxylic acid anhydride groups, and carbon-carbon double bond groups.
[0058] Furthermore, the undercoat layer may further contain electron transport materials, metal oxide particles, metal particles, conductive polymers, etc., for the purpose of improving electrical properties. Among these, electron transport materials and metal oxide particles are preferred. Examples of electron transport materials include quinone compounds, imide compounds, benzimidazole compounds, cyclopentadienylidene compounds, fluorenone compounds, xanthone compounds, benzophenone compounds, cyanovinyl compounds, aryl halides, silole compounds, and boron-containing compounds. An electron transport material having polymerizable functional groups may be used as the electron transport material, and a base layer may be formed as a cured film by copolymerizing it with the above-mentioned monomers having polymerizable functional groups. Examples of metal oxide particles include indium tin oxide, tin oxide, indium oxide, titanium oxide, strontium titanate, zinc oxide, and aluminum oxide. Silicon dioxide particles can also be used. Examples of metal particles include gold, silver, and aluminum. The metal oxide particles contained in the undercoat may be surface-treated using a surface treatment agent such as a silane coupling agent before use.
[0059] Common methods are used for surface treatment of metal oxide particles. Examples include dry and wet methods. The dry method involves adding an aqueous alcohol solution, an organic solvent solution, or an aqueous solution containing a surface treatment agent to metal oxide particles while stirring them in a high-speed mixer such as a Henschel mixer, then uniformly dispersing them and drying them. In the wet method, metal oxide particles and a surface treatment agent are stirred in a solvent or dispersed using glass beads or the like in a sand mill. After dispersion, the solvent is removed by filtration or reduced-pressure distillation. After solvent removal, it is preferable to further bake the mixture at 100°C or higher.
[0060] The undercoat layer may further contain additives, such as known materials including metal particles like aluminum particles, conductive material particles like carbon black, charge transport materials, metal chelate compounds, and organometallic compounds.
[0061] The undercoat layer can be formed by preparing an undercoat coating solution containing the above-mentioned materials and solvents, forming this coating film on a support or conductive layer, and then drying and / or curing it. Examples of solvents used in the coating liquid for the undercoat include organic solvents such as alcohols, sulfoxides, ketones, ethers, esters, aliphatic halogenated hydrocarbons, and aromatic compounds. In this disclosure, it is preferable to use alcohol-based or ketone-based solvents.
[0062] Dispersion methods for preparing coating liquids for the undercoat include methods using homogenizers, ultrasonic dispersers, ball mills, sand mills, roll mills, vibratory mills, attritors, and liquid impact type high-speed dispersers.
[0063] The thickness of the undercoat layer is preferably 0.1 μm or more and 50 μm or less, more preferably 0.2 μm or more and 40 μm or less, and particularly preferably 0.3 μm or more and 30 μm or less.
[0064] <Photosensitive layer> The photosensitive layers of electrophotographic photoreceptors are mainly classified into (1) multilayer photosensitive layers and (2) single-layer photosensitive layers. (1) A multilayer photosensitive layer is a photosensitive layer having a charge generating layer containing a charge generating material and a charge transport layer containing a charge transport material. (2) A single-layer photosensitive layer is a photosensitive layer containing both a charge generating material and a charge transport material.
[0065] (1) Stacked photosensitive layer The stacked photosensitive layer comprises a charge generation layer and a charge transport layer.
[0066] (1-1) Charge generation layer The charge generation layer preferably contains a charge generation material and a resin.
[0067] Examples of charge-generating materials include azo pigments, perylene pigments, polycyclic quinone pigments, indigo pigments, and phthalocyanine pigments. Among these, azo pigments and phthalocyanine pigments are preferred. Among phthalocyanine pigments, oxytitanium phthalocyanine pigments, chlorogallium phthalocyanine pigments, and hydroxygallium phthalocyanine pigments are preferred. The content of the charge generating material in the charge generating layer is preferably 40% to 85% by mass, and more preferably 60% to 80% by mass, relative to the total mass of the charge generating layer.
[0068] Examples of resins include polyester resin, polycarbonate resin, polyvinyl acetal resin, polyvinyl butyral resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenolic resin, polyvinyl alcohol resin, cellulose resin, polystyrene resin, polyvinyl acetate resin, and polyvinyl chloride resin. Among these, polyvinyl butyral resin is more preferred.
[0069] Furthermore, the charge generation layer may further contain additives such as antioxidants and ultraviolet absorbers. Specifically, examples include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, and the like.
[0070] The charge generation layer can be formed by preparing a coating solution for the charge generation layer containing the above-mentioned materials and solvents, forming this coating film on the undercoat layer, and drying it. Examples of solvents used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.
[0071] The thickness of the charge generation layer is preferably 0.1 μm or more and 1 μm or less, and more preferably 0.15 μm or more and 0.4 μm or less.
[0072] (1-2) Charge transport layer The charge transport layer preferably contains a charge transport material and a resin as a binder.
[0073] Examples of charge transport materials include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzicine compounds, triarylamine compounds, and resins having groups derived from these substances. Among these, triarylamine compounds and benzicine compounds are preferred. The content of the charge transport material in the charge transport layer is preferably 25% by mass or more and 70% by mass or less, and more preferably 30% by mass or more and 55% by mass or less, based on the total mass of the charge transport layer.
[0074] Examples of resins include polyester resin, polycarbonate resin, acrylic resin, and polystyrene resin. Among these, polycarbonate resin and polyester resin are preferred. Polyarylate resin is particularly preferred among polyester resins. The content ratio (mass ratio) of the charge transport material to the resin is preferably 4:10 to 20:10, and more preferably 5:10 to 12:10.
[0075] If the protective layer described later is not provided, the charge transport layer becomes the surface layer. In this case, the charge transport layer contains fluorine atom-containing resin particles, a binder material, and polymer A having the structural unit shown in formula (1) above. Furthermore, the content of fluorine atom-containing resin particles in the charge transport layer is preferably 5% by mass or more and 40% by mass or less of the total mass of the charge transport layer, from the viewpoint of improving the uniformity of the dispersion of fluorine atom-containing resin particles and improving wear resistance. Moreover, the content of fluorine atom-containing resin particles in the charge transport layer is more preferably 5% by mass or more and 15% by mass or less, and even more preferably 7% by mass or more and 10% by mass or less.
[0076] In particular, when the charge transport layer is the surface layer, the binder material contains a thermoplastic resin, the surface layer further contains a charge transport substance, and the thermoplastic resin is preferably at least one resin selected from a polycarbonate resin and a polyarylate resin.
[0077] Also, it is preferable that the charge transport substance is at least one compound selected from the compound represented by the following formula (4) and the compound represented by the following formula (5).
Chemical formula
Chemical formula
[0078] The charge transport layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, lubrication agents, and wear resistance enhancers. Specifically, examples include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles.
[0079] The charge transport layer can be formed by preparing a coating solution for the charge transport layer containing the above-mentioned materials and solvents, forming this coating film on the charge generating layer, and drying it. Examples of solvents used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Among these solvents, ether-based solvents or aromatic hydrocarbon-based solvents are preferred.
[0080] The thickness of the charge transport layer is preferably 5 μm to 50 μm, more preferably 8 μm to 40 μm, and particularly preferably 10 μm to 30 μm.
[0081] (2) Single-layer photosensitive layer A single-layer photosensitive layer can be formed by preparing a coating solution for a photosensitive layer containing a charge generating substance, a charge transporting substance, a resin, and a solvent, forming this coating film on an undercoat layer, and drying it. The charge generating substance, charge transporting substance, and resin are the same as the examples of materials in "(1) Multilayer Photosensitive Layer" above.
[0082] If the protective layer described later is not provided, the single-layer photosensitive layer becomes the surface layer. In this case, the single-layer photosensitive layer contains fluorine atom-containing resin particles, a binder material, and polymer A having the structural unit shown in formula (1) above.
[0083] <Protective layer> In this invention, a protective layer may be provided on the photosensitive layer. Providing a protective layer can improve durability. When a protective layer is provided, the protective layer becomes the surface layer. In this case, the protective layer contains fluorine atom-containing resin particles, a binder material, and polymer A having the structural unit shown in formula (1) above.
[0084] The protective layer may be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group. Here, the monomer having a polymerizable functional group is a raw material for the binder, and the cured product of the monomer having a polymerizable functional group is the binder contained in the protective layer. Examples of reactions when polymerizing a composition containing a monomer having a polymerizable functional group include thermal polymerization, photopolymerization, and radiation polymerization. Examples of polymerizable functional groups in a monomer having a polymerizable functional group include isocyanate groups, blocked isocyanate groups, methylol groups, alkylated methylol groups, epoxy groups, metal alkoxide groups, hydroxyl groups, amino groups, carboxyl groups, thiol groups, carboxylic acid anhydride groups, and groups containing carbon-carbon double bonds. Examples of groups containing carbon-carbon double bonds include acryloyl groups and methacryloyl groups. A monomer having charge transport ability may be used as the monomer having a polymerizable functional group.
[0085] When a protective layer is provided, the protective layer becomes the surface layer of the electrophotographic photoreceptor. In this case, the protective layer contains fluorine atom-containing resin particles, a binder material, and polymer A having the structural unit shown in formula (1) above.
[0086] The protective layer may contain additives such as antioxidants, UV absorbers, plasticizers, and leveling agents. Specifically, examples of additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, and silicone oils.
[0087] The protective layer can be formed by preparing a protective coating solution containing the above-mentioned materials and solvents, forming this coating film on the photosensitive layer, and then drying and / or curing it. Examples of solvents used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, sulfoxide-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.
[0088] The thickness of the protective layer is preferably 0.5 μm to 10 μm, and more preferably 1 μm to 7 μm.
[0089] One preferred form of the protective layer is when the binder material includes a cured product of a hole-transporting compound having polymerizable functional groups.
[0090] The hole-transporting compound having a polymerizable functional group is preferably at least one compound selected from the compounds represented by the following formula (CT-1) and the compounds represented by the following formula (CT-2). [ka] (In formula (CT-1), Ar 11 ~Ar 13 Each of these independently represents an aryl group which may have substituents, and the substituents which may have substituents are alkyl groups having 1 to 6 carbon atoms, and monovalent functional groups represented by any of the following formulas (P-1) to (P-3). However, the compound represented by formula (CT-1) has at least one aryl group having a monovalent functional group as a substituent, as shown in any of the following formulas (P-1) to (P-3). [ka] (In formula (CT-2), Ar 21 ~Ar 24 Each of these independently represents an aryl group which may have substituents, and the substituents which may have substituents are alkyl groups having 1 to 6 carbon atoms, and monovalent functional groups represented by any of the following formulas (P-1) to (P-3). Ar 25 represents an arylene group which may have a substituent, and the substituent which the arylene group may have is an alkyl group having 1 to 6 carbon atoms and a monovalent functional group represented by any one of the following formulas (P-1) to (P-3). However, the compound represented by the formula (CT-2) has at least one group selected from an aryl group having a monovalent functional group represented by any one of the following formulas (P-1) to (P-3) as a substituent and an arylene group having a monovalent functional group represented by any one of the following formulas (P-1) to (P-3) as a substituent.)
Chemical formula
Chemical formula
Chemical formula
[0091] In the protective layer according to this embodiment, the content ratio of the fluorine atom-containing resin particles in the protective layer is preferably 5% by mass or more and 40% by mass or less with respect to the total mass of the protective layer from the viewpoints of improving the uniformity of dispersion of the fluorine atom-containing resin particles and improving the abrasion resistance. Further, the content ratio of the fluorine atom-containing resin particles in the protective layer is more preferably 20% by mass or more and 40% by mass or less, and still more preferably 25% by mass or more and 35% by mass or less.
[0092] It should be noted that there seems to be an error in the numbering of "二十一" and "二十二" in the original text. I have translated it as is for now. If this is a misnumbering in the original, please correct it for a more accurate translation.Another preferred form of the protective layer is when the binder material comprises a cured product of a charge-transporting compound and at least one triazine compound selected from guanamine compounds and melamine compounds.
[0093] In this disclosure, a charge-transporting compound is a compound having an organic group derived from a compound having charge-transporting ability, and at least one polymerizable functional group. Polymerizable functional groups found in charge-transporting compounds include hydroxyl groups (-OH), methylol groups (-CH2OH), methoxy groups (-OCH3), amino groups (-NH2), thiol groups (-SH), and carboxyl groups (-COOH). The charge-transporting compound preferably has at least one polymerizable functional group selected from among methylol groups and methoxy groups.
[0094] Among the organic groups derived from compounds with charge transport ability, arylamine derivatives are preferred as compounds with charge transport ability. Examples of arylamine derivatives include triphenylamine derivatives and tetraphenylbenzidine derivatives.
[0095] Specific examples of charge-transporting compounds include the following: [ka] [ka]
[0096] In particular, the protective layer preferably contains at least one triazine compound selected from the guanamine compound represented by formula (A) and the melamine compound represented by formula (B) below. [ka] (In formula (A), R 101 ~R 104Each of these independently represents a hydrogen atom, a hydroxymethyl group, or an alkoxymethyl group, and R 101 ~R 104 At least one of them is a hydroxymethyl group or an alkoxymethyl group, R 105 This represents an alkyl group which may have substituents, a phenyl group which may have substituents, or a cycloalkyl group which may have substituents. R 105 The substituents that the alkyl group, phenyl group, and cycloalkyl group shown may each have are alkyl groups and alkoxy groups. [ka] (In formula (B), R 201 ~R 206 Each of these independently represents a hydrogen atom, a hydroxymethyl group, an alkoxymethyl group, or an alkoxy group, and R 201 ~R 206 At least one of them is a hydroxymethyl group, an alkoxymethyl group, or an alkoxy group.
[0097] The protective layer contains at least one triazine compound selected from the guanamine compound represented by formula (A) and the melamine compound represented by formula (B), thereby improving the film strength. Furthermore, since these compounds have nitrogen atoms that contribute to electron transport, the electron transport performance in the protective layer is improved. A triazine compound refers to a compound containing a triazine ring, and in the present invention, it is a guanamine compound or a melamine compound.
[0098] The cured product of the charge-transporting compound (a) and triazine compound (b) contained in the protective layer is preferably a cured product obtained by reacting b:a = 1:3 to 1:300 (molar ratio). From the viewpoint of surface layer abrasion resistance, a b / a ratio of 1 / 100 or more is more preferable, and from the viewpoint of suppressing potential fluctuations due to repeated use, a b / a ratio of 1 / 5 or less is more preferable.
[0099] In the protective layer according to this embodiment, the content of fluorine atom-containing resin particles in the protective layer is preferably 5% by mass or more and 40% by mass or less with respect to the total mass of the protective layer, from the viewpoint of improving the uniformity of the dispersion of fluorine atom-containing resin particles and improving wear resistance. Furthermore, the content of fluorine atom-containing resin particles in the protective layer is more preferably 5% by mass or more and 15% by mass or less, and even more preferably 7% by mass or more and 12% by mass or less.
[0100] Commercially available guanamine compounds include Super Beccamine L-148-55, Super Beccamine 13-535, Super Beccamine L-145-60, Super Beccamine TD-126 (all manufactured by DIC Corporation), and Nikalac BL-60 and Nikalac BX-4000 (both manufactured by Sanwa Chemical Co., Ltd.).
[0101] Commercially available melamine compounds include Super Melami No. 90 (manufactured by NOF Corporation), Super Beccamine TD-139-60 (manufactured by DIC Corporation), Yuban 2020 (manufactured by Mitsui Chemicals), Sumitex Resin M-3 (manufactured by Sumitomo Chemical Co., Ltd.), and Nikalac MW-30 (manufactured by Sanwa Chemical Co., Ltd.).
[0102] <Surface treatment of electrophotographic photoreceptors> In this disclosure, the surface of the electrophotographic photoreceptor may be processed. By processing the surface, the behavior of the cleaning means (cleaning blade) that comes into contact with the electrophotographic photoreceptor can be made more stable. Methods of surface processing include pressing a mold having protrusions onto the surface of the electrophotographic photoreceptor to transfer the shape, creating uneven surfaces by mechanical polishing, or roughening the surface by impacting it with powder. In this way, by providing recesses or protrusions on the surface layer of the electrophotographic photoreceptor, the behavior of the cleaning means that comes into contact with the electrophotographic photoreceptor can be made more stable.
[0103] The recesses or protrusions may be formed over the entire surface of the electrophotographic photoreceptor, or on a portion of the surface of the electrophotographic photoreceptor. If the recesses or protrusions are formed on a portion of the surface of the electrophotographic photoreceptor, it is preferable that the recesses or protrusions are formed over at least the entire contact area with the cleaning means (cleaning blade).
[0104] When forming a recess, a mold having a convex portion corresponding to the recess is pressed against the surface of the electrophotographic photoreceptor, and the shape is transferred, thereby forming a recess on the surface of the electrophotographic photoreceptor.
[0105] <Abrasive tools used for mechanical polishing> Mechanical polishing can be performed using known methods. Generally, a polishing tool is brought into contact with an electrophotographic photoreceptor, and one or both of the tools are moved relative to each other to polish the surface of the electrophotographic photoreceptor. The polishing tool is a polishing member having a layer on a base material in which abrasive particles are dispersed in a binder resin.
[0106] Examples of abrasive particles include aluminum oxide, chromium oxide, diamond, iron oxide, cerium oxide, corundum, silica, silicon nitride, boron nitride, molybdenum carbide, silicon carbide, tungsten carbide, titanium carbide, and silicon oxide. The particle size of the abrasive particles is preferably 0.01 μm to 50 μm, and more preferably 1 μm to 15 μm. If the particle size of the abrasive particles is too small, the polishing power will be weak, and it will be difficult to increase the F / C ratio of the outermost surface of the electrophotographic photoreceptor. These abrasive particles can be used individually or in mixtures of two or more types. When mixing two or more types, the materials and particle sizes may differ from each other.
[0107] As the binder resin for dispersing abrasive particles used in polishing tools, known thermoplastic resins, thermosetting resins, reactive resins, electron beam curing resins, ultraviolet curing resins, visible light curing resins, and antifungal resins can be used. Examples of thermoplastic resins include vinyl chloride resin, polyamide resin, polyester resin, polycarbonate resin, amino resin, styrene-butadiene copolymer, urethane elastomer, and polyamide-silicone resin. Examples of thermosetting resins include phenolic resin, phenoxy resin, epoxy resin, polyurethane resin, polyester resin, silicone resin, melamine resin, and alkyd resin. An isocyanate-based curing agent may also be added to the thermoplastic resin.
[0108] The thickness of the layer formed by dispersing abrasive grains in the binder resin of the polishing tool is preferably between 1 μm and 100 μm. If the thickness is too thick, unevenness in thickness is likely to occur, resulting in uneven surface roughness of the workpiece. On the other hand, if the thickness is too thin, the abrasive grains are more likely to fall off.
[0109] The shape of the base material of the polishing tool is not particularly limited. In the embodiments of this disclosure, a sheet-like base material was used to efficiently polish a cylindrical electrophotographic photoreceptor, but other shapes may also be used. (Hereafter, the polishing tool of this disclosure will also be referred to as a polishing sheet.) The material of the base material of the polishing tool is also not particularly limited. For example, the material of the sheet-like base material may be paper, woven fabric, nonwoven fabric, or plastic film.
[0110] The polishing tool can be obtained by coating a substrate with a paint mixture in which the above-mentioned abrasive grains, binder resin, and solvent capable of dissolving the binder resin are mixed and dispersed, and then drying the mixture.
[0111] <Polishing equipment> Figure 2 shows an example of a polishing apparatus for surface processing of electrophotographic photoreceptors. Figure 2 shows an apparatus for polishing a cylindrical electrophotographic photoreceptor using a polishing sheet. In Figure 2, the polishing sheet 2-1 is wound around a hollow shaft 2-6, and a motor (not shown) is positioned so that tension is applied to the polishing sheet 2-1 in the opposite direction to the direction in which the polishing sheet 2-1 is fed to the shaft 2-6. The polishing sheet 2-1 is fed in the direction of the arrow, passes through guide rollers 2-2a and 2-2b to a backup roller 2-3, and after polishing, the polishing sheet 2-1 is wound onto a winding means 2-5 by a motor (not shown) via guide rollers 2-2c and 2-2d. Polishing is performed by constantly pressing the polishing sheet 2-1 against the workpiece (electrophotographic photoreceptor before polishing) 2-4. Since the polishing sheet 2-1 is often insulating, it is preferable to use a material that is grounded or conductive at the contact points of the polishing sheet 2-1.
[0112] The feed speed of the abrasive sheet 2-1 is preferably in the range of 10 mm / min to 1000 mm / min. If the feed rate is too low, the binder resin may adhere to the surface of the abrasive sheet 2-1, which may result in deep scratches on the surface of the workpiece 2-4.
[0113] The workpiece 2-4 is placed facing the backup roller 2-3 via the abrasive sheet 2-1. The backup roller 2-3 is preferably elastic in order to improve the uniformity of the surface roughness of the workpiece 2-4. In this process, the workpiece 2-4 and the backup roller 2-3 are pressed together for a predetermined time at a desired setting value via the abrasive sheet 2-1, and the surface of the workpiece 2-4 is polished. The rotation direction of the workpiece 2-4 may be the same as the direction in which the abrasive sheet 2-1 is fed, or it may be opposite. Furthermore, the rotation direction may be changed during polishing.
[0114] The pressure applied by the backup rollers 2-3 against the workpiece 2-4 depends on the hardness of the backup rollers 2-3 and the polishing time, but is approximately 0.005 N / m 2 More than 15N / m 2 The following are preferable.
[0115] The surface roughness of the electrophotographic photoreceptor can be adjusted by appropriately selecting the feed speed of the polishing sheet 2-1, the pressing pressure of the backup roller 2-3, the abrasive grain type of the polishing sheet, the film thickness of the binder resin of the polishing sheet, the thickness of the substrate, etc.
[0116] <Measurement of the maximum height Rmax in JIS B0601 1982> The surface roughness of the electrophotographic photoreceptor can be measured by known means. For example, the following can be mentioned. Surface roughness meters such as the Surf Coader SE3500 type surface roughness measuring instrument manufactured by Kosaka Laboratory Ltd. Non-contact three-dimensional surface measuring machine Micro Map 557N manufactured by Hishikawa System Co., Ltd. Microscopes capable of acquiring three-dimensional shapes such as the ultra-depth shape measuring microscope VK-8550 and VK-9000 manufactured by Keyence Corporation.
[0117] In the present disclosure, among the indices of surface roughness, the maximum height Rmax in JIS B0601 1982 defined by the Japanese Industrial Standard JIS is used as the polishing depth L (μm). Further, in the present disclosure, for the range of a 5 mm square section of the electrophotographic photoreceptor cut out as a specimen for X-ray photoelectron spectroscopy described later, Rmax is measured in advance. The measurement is performed arbitrarily at three locations within the range of 5 mm square, and the average value is adopted as the polishing depth L (μm).
[0118] <Process cartridge, electrophotographic apparatus> The electrophotographic photoreceptor according to the present disclosure may be one of the components of a process cartridge or an electrophotographic apparatus. The process cartridge according to the present disclosure integrally supports at least one means selected from the group consisting of the electrophotographic photoreceptor described so far, a charging means, a developing means, and a cleaning means, and is detachable from the electrophotographic apparatus main body. Further, the electrophotographic apparatus according to the present disclosure has the electrophotographic photoreceptor described so far, as well as a charging means, an exposure means, a developing means, and a transfer means.
[0119] An example of the configuration of a process cartridge according to this disclosure is shown in Figure 3. In Figure 3, the cylindrical electrophotographic photoreceptor 1 is driven to rotate at a predetermined peripheral speed in the direction of the arrow. The peripheral surface of the rotating electrophotographic photoreceptor 1 is uniformly charged to a predetermined positive or negative potential by the charging means 2. Next, the charged peripheral surface of the electrophotographic photoreceptor 1 receives exposure light (image exposure light) 3 output from an exposure means (not shown), such as slit exposure or laser beam scanning exposure. In this way, an electrostatic latent image corresponding to the target image is sequentially formed on the peripheral surface of the electrophotographic photoreceptor 1. The voltage applied to the charging means (charging roller, etc.) 2 may be either a voltage with an AC component superimposed on a DC component, or a voltage with only a DC component.
[0120] The electrostatic latent image formed on the circumferential surface of the electrophotographic photoreceptor 1 is developed by the toner contained in the developer of the developing means 4 to form a toner image. Next, the toner image formed and supported on the circumferential surface of the electrophotographic photoreceptor 1 is sequentially transferred to the transfer material (paper, intermediate transfer material, etc.) 6 by the transfer bias from the transfer means (transfer roller, etc.) 5. The transfer material 6 is fed in synchronization with the rotation of the electrophotographic photoreceptor 1.
[0121] After toner image transfer, the surface of the electrophotographic photoreceptor 1 is treated to remove static electricity by pre-exposure light 7 from a pre-exposure means (not shown), and then cleaned by a cleaning means 8 to remove any remaining toner. The electrophotographic photoreceptor 1 is then repeatedly used for image formation. The pre-exposure means may be performed before or after the cleaning process, and is not necessarily required.
[0122] The electrophotographic photoreceptor 1 may be mounted in an electrophotographic device such as a copier or a laser beam printer. Alternatively, a process cartridge 9 may be constructed by housing and supporting multiple components, such as the electrophotographic photoreceptor 1, charging means 2, developing means 4, and cleaning means 8, in a container, and making it detachable from the electrophotographic device body. In Figure 3, the electrophotographic photoreceptor 1, charging means 2, developing means 4, and cleaning means 8 are supported as a single unit, forming a process cartridge 9 that is detachable from the electrophotographic device body.
[0123] Next, an electrophotographic apparatus equipped with the electrophotographic photoreceptor of the present invention will be described. Figure 4 shows an example of the configuration of the electrophotographic apparatus according to this disclosure. A process cartridge 17 for yellow, a process cartridge 18 for magenta, a process cartridge 19 for cyan, and a process cartridge 20 for black are arranged side by side along an intermediate transfer body 10. These process cartridges correspond to yellow, magenta, cyan, and black, respectively. The diameter and constituent materials of the electrophotographic photoreceptor, the developer, the charging method, and other means do not necessarily have to be the same for each color.
[0124] When the image formation operation begins, toner images of each color are sequentially superimposed on the intermediate transfer body 10 according to the image formation process described above. In parallel, the transfer paper 11 is fed from the paper tray 13 by the paper feed path 12 and is fed to the secondary transfer means 14 in time with the rotation of the intermediate transfer body. The toner image on the intermediate transfer body 10 is transferred to the transfer paper 11 by the transfer bias from the secondary transfer means 14. The toner image transferred onto the transfer paper 11 is transported along the paper feed path 12, fixed onto the transfer paper by the fixing means 15, and then discharged from the paper discharge unit 16.
[0125] The electrophotographic photoreceptor relating to this disclosure can be used in laser beam printers, LED printers, copiers, facsimile machines, and multifunction devices thereof. [Examples]
[0126] The present disclosure will be described in further detail below using examples and comparative examples, but will not be limited thereto. In the following descriptions of examples, "parts" refers to mass unless otherwise specified.
[0127] <Synthesis of polymer A having the structural unit shown in formula (1)> The polymer A having the structural unit represented by formula (1) above (hereinafter also referred to as "graft copolymer") in this disclosure was synthesized as follows. The acrylate compound and macromonomer compound used in the following synthesis example can be produced, for example, by referring to Japanese Patent Application Publication No. 2009-104145.
[0128] (Graft copolymer 1) The following materials were prepared. 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate • 75 parts of the macromonomer represented by the following formula (D) (macromonomer AA-6) (number-average molecular weight 6,000) • 1,1'-Azobis(1-acetoxy-1-phenylethane) (Trade name: OTAZO-15, manufactured by Otsuka Chemical Co., Ltd.) 0.437 parts • 338 parts n-butyl acetate These were mixed in a glass flask equipped with a stirrer, reflux condenser, nitrogen gas inlet tube, constant temperature bath, and thermometer at 20°C under a nitrogen atmosphere for 30 minutes. The reaction mixture was then heated to 85-90°C and allowed to react for 5 hours. The reaction was stopped by ice cooling, and 1500 parts by mass of 2-propanol was added to obtain a precipitate. This precipitate was washed with a mixed solvent of n-butyl acetate and 2-propanol in a ratio of 1:5, and dried at 80°C under reduced pressure of 1325 Pa or less for 3 hours to obtain graft copolymer 1. [ka]
[0129] (Graft copolymer 2) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 55 parts of 2-(difluoro(1,1,2,2,3,3-hexafluoro-3-(perfluoropropoxy)propoxy)methoxy)-2,2-difluoroethyl acrylate). Graft copolymer 2 was obtained in the same manner as graft copolymer 1.
[0130] (Graft copolymer 3) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 62 parts of 3,3,4,4,-tetrafluoro-4-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)butyl acrylate. Graft copolymer 3 was obtained in the same manner as graft copolymer 1.
[0131] (Graft copolymer 4) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 61 parts of 2-(difluoro(1,1,2,2-tetrafluoro-2-((perfluoropentyl)oxy)ethoxy)methoxy)-2,2-difluoroethyl acrylate). Otherwise, graft copolymer 4 was obtained in the same manner as graft copolymer 1.
[0132] (Graft copolymer 5) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 45 parts of 2-((difluoro(perfluoropropoxy)methoxy)difluoromethoxy)-2,2-difluoroethyl acrylate). Otherwise, graft copolymer 5 was obtained in the same manner as graft copolymer 1.
[0133] (Graft copolymer 6) In the synthesis of graft copolymer 1, the amount of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate used was changed to 30 parts. Also, the amount of macromonomer AA-6 used was changed to 300 parts. Graft copolymer 6 was obtained in the same manner as graft copolymer 1.
[0134] (Graft copolymer 7) In the synthesis of graft copolymer 1, the amount of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate used was changed to 42 parts. In addition, the amount of macromonomer AA-6 used was changed to 180 parts. Graft copolymer 7 was obtained in the same manner as graft copolymer 1.
[0135] (Graft copolymer 8) In the synthesis of graft copolymer 1, the amount of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate used was changed to 68 parts. Otherwise, graft copolymer 8 was obtained in the same manner as graft copolymer 1.
[0136] (Graft copolymer 9) In the synthesis of graft copolymer 1, the amount of 1,1'-azobis(1-acetoxy-1-phenylethane) used was changed to 0.862 parts. Otherwise, graft copolymer 9 was obtained in the same manner as graft copolymer 1.
[0137] (Graft copolymer 10) In the synthesis of graft copolymer 1, the amount of 1,1'-azobis(1-acetoxy-1-phenylethane) used was changed to 0.764 parts. Otherwise, graft copolymer 10 was obtained in the same manner as graft copolymer 1.
[0138] (Graft copolymer 11) In the synthesis of graft copolymer 1, the amount of 1,1'-azobis(1-acetoxy-1-phenylethane) used was changed to 0.183 parts. Otherwise, graft copolymer 11 was obtained in the same manner as graft copolymer 1.
[0139] (Graft copolymer 12) In the synthesis of graft copolymer 1, the amount of 1,1'-azobis(1-acetoxy-1-phenylethane) used was changed to 0.131 parts. Otherwise, graft copolymer 12 was obtained in the same manner as graft copolymer 1.
[0140] (Graft copolymer 13) In the synthesis of graft copolymer 1, the amount of 1,1'-azobis(1-acetoxy-1-phenylethane) used was changed to 0.922 parts. Otherwise, graft copolymer 13 was obtained in the same manner as graft copolymer 1.
[0141] (Graft copolymer 14) In the synthesis of graft copolymer 1, the amount of 1,1'-azobis(1-acetoxy-1-phenylethane) used was changed to 0.127 parts. Otherwise, graft copolymer 14 was obtained in the same manner as graft copolymer 1.
[0142] (Graft copolymer 15) In the synthesis of graft copolymer 1, the amount of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate used was changed to 24 parts. In addition, the amount of macromonomer AA-6 used was changed to 360 parts. Graft copolymer 15 was obtained in the same manner as graft copolymer 1.
[0143] (Graft copolymer 16) In the synthesis of graft copolymer 1, the amount of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate used was changed to 60 parts. Also, the amount of macromonomer AA-6 used was changed to 30 parts. Otherwise, graft copolymer 16 was obtained in the same manner as graft copolymer 1.
[0144] (Graft copolymer 17) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 40 parts of 2-((difluoro(perfluoroethoxy)methoxy)difluoromethoxy)-2,2-difluoroethyl acrylate). Otherwise, graft copolymer 17 was obtained in the same manner as for graft copolymer 1.
[0145] (Graft copolymer 18) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 65 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,3,3,3-hexafluoro-2-(perfluoropropoxy)propoxy)ethoxy)propyl acrylate. Otherwise, graft copolymer 18 was obtained in the same manner as graft copolymer 1.
[0146] (Graft copolymer 19) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 59 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,3,3,3-hexafluoro-2-(perfluorobutoxy)propoxy)propyl acrylate. Otherwise, graft copolymer 19 was obtained in the same manner as graft copolymer 1.
[0147] (Graft copolymer 20) In the synthesis of graft copolymer 1, 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate was replaced with 2-((difluoro((perfluorohexyl)oxy)methoxy)difluoromethoxy)-2,2-difluoroethyl acrylate). Otherwise, graft copolymer 20 was obtained in the same manner as for graft copolymer 1.
[0148] (Graft copolymer 21) In the synthesis of graft copolymer 1, 60 parts of 2,2,3,3-tetrafluoro-3-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)propyl acrylate were replaced with 63 parts of 4,4,5,5-tetrafluoro-5-(1,1,2,2-tetrafluoro-2-(1,1,2,2-tetrafluoro-2-(perfluoropropoxy)ethoxy)ethoxy)pentyl acrylate. Otherwise, graft copolymer 21 was obtained in the same manner as graft copolymer 1.
[0149] Table 4 shows the composition and weight-average molecular weight of the obtained graft copolymers 1-21. The weight-average molecular weight of the graft copolymers was calculated by GPC using the method described above. Note that in Table 4, multiple Rf 1 This is the Rf at the end of the graft copolymer, closer to the main chain. 2 (Farthest from) Rf 1-1 , Rf 1-2 , and Rf 1-3 As shown.
[0150] [Table 4]
[0151] <Fabrication of electrophotographic photoreceptors> [Example 1-1] (Support 1) As a support (conductive support), a cylindrical aluminum cylinder (JIS-A3003, aluminum alloy, outer diameter 30.6 mm, length 370 mm, wall thickness 1 mm) that had been machined was used. Ultrasonic cleaning was performed in a cleaning solution containing detergent (product name: Chemicol CT, manufactured by Tokiwa Chemical Co., Ltd.) in pure water, followed by rinsing off the cleaning solution, and then further ultrasonic cleaning in pure water to degrease it, and this was used as support 1.
[0152] (Bottom layer 1) Zinc oxide particles (specific surface area: 19 m²) 2 / g, powder resistance: 4.7×10 6100 parts of (Ω·cm) were mixed with 500 parts of toluene by stirring. 0.8 parts of a silane coupling agent (compound name: N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, trade name: KBM602, manufactured by Shin-Etsu Chemical Co., Ltd.) were added to the resulting mixture and stirred for 6 hours. Subsequently, the toluene was removed by distillation under reduced pressure, and the mixture was heated and dried at 130°C for 6 hours to obtain surface-treated zinc oxide particles A.
[0153] Next, 15 parts of butyral (trade name: BM-1, manufactured by Sekisui Chemical Co., Ltd.) and 15 parts of blocked isocyanate (trade name: Duranate TPA-B80E, non-volatile content 80% by mass, manufactured by Asahi Kasei Chemicals Corporation) were prepared as polyols. These were dissolved in a mixed solvent of 73.5 parts methyl ethyl ketone and 73.5 parts 1-butanol. To this solution, 80.8 parts of surface-treated zinc oxide particles A and 0.81 parts of 2,3,4-trihydroxybenzophenone (manufactured by Tokyo Chemical Industry Co., Ltd.) were added, and the mixture was dispersed for 3 hours at a 23±3°C atmosphere using a sand mill apparatus with glass beads with a diameter of 0.8 mm.
[0154] Next, we prepared the following materials. • Silicone oil (product name: SH28PA, manufactured by Toray Dow Corning Co., Ltd. (formerly Toray Dow Corning Silicone Co., Ltd.)) 0.01 parts • Cross-linked polymethyl methacrylate (PMMA) particles (product name: Techpolymer SSX-103, manufactured by Sekisui Chemical Co., Ltd., average primary particle size: 3 μm) 5.6 parts These were added to the solution after the dispersion treatment described above and stirred to prepare the coating solution for the undercoat layer. The obtained undercoating solution was applied to the support 1 by immersion to form a coating film, and the coating film was dried at 160°C for 30 minutes to form an undercoat 1 with a thickness of 18 μm.
[0155] (Charge generation layer 1) The following materials were prepared. • Four portions of hydroxygallium phthalocyanine crystals (charge-generating material) in a crystalline form exhibiting strong peaks at Bragg angles of 2θ±0.2°, specifically at 7.4° and 28.1°, in CuKα characteristic X-ray diffraction. • 0.04 parts of the compound represented by the following formula (E) These were added to a solution prepared by dissolving 2 parts of polyvinyl butyral (product name: Esrec BX-1, manufactured by Sekisui Chemical Co., Ltd.) in 100 parts of cyclohexanone. Subsequently, the mixture was dispersed for 1 hour in a sand mill using 1 mm diameter glass beads at an atmosphere of 23 ± 3°C. After dispersion, 100 parts of ethyl acetate were added to prepare a coating solution for the charge generation layer. This charge generation layer coating solution was applied to the undercoat layer 1 by immersion, and the resulting coating film was dried at 90°C for 10 minutes to form a charge generation layer 1 with a thickness of 0.13 μm. [ka]
[0156] (Charge transport layer 1) The following materials were prepared. 60 parts of the compound represented by the following formula (F) 30 parts of the compound represented by the following formula (G) • 10 parts of the compound represented by the following formula (H) 100 units of bisphenol Z-type polycarbonate resin (product name: Yupiron Z400, manufactured by Mitsubishi Engineering Plastics Corporation) 0.2 parts of polycarbonate having the unit shown in formula (I) below (viscosity-average molecular weight Mv: 20000) These were dissolved in a mixed solvent of 272 parts o-xylene, 256 parts methyl benzoate, and 272 parts dimethoxymethane to prepare a coating solution for the charge transport layer. This charge transport layer coating solution was applied to the charge generating layer 1 by immersion to form a coating film, and the resulting coating film was dried at 115°C for 50 minutes to form a charge transport layer 1 with a thickness of 18 μm. [ka] [ka] [ka] [Chemical formula] (In formula (I), 0.95 and 0.05 are the molar ratios (copolymerization ratios) of two units.)
[0157] (Protective layer) 2.20 parts of graft copolymer 1 was dissolved in a mixed solvent consisting of 100 parts of 1,1,2,2 - tetrafluoroethyl - 2,2,2 - trifluoroethyl ether (trade name: AE - 3000, manufactured by AGC Inc.) and 100 parts of 1 - propanol to prepare a dispersant solution. 40 parts of polytetrafluoroethylene resin particles (average primary particle diameter 210 nm, average circularity 0.85) were added to the obtained dispersant solution. Then, it was passed through a high - pressure homogenizer (trade name: Microfluidizer M - 110EH, manufactured by Microfluidics Corp., USA) to obtain a polytetrafluoroethylene resin particle dispersion.
[0158] 75.4 parts of a hole - transporting compound represented by the following formula (J), 21.9 parts of a compound represented by the following formula (K), and 100 parts of 1 - propanol were added to the obtained polytetrafluoroethylene resin particle dispersion. Then, filtration was performed using a polypropylene filter (trade name: PF - 040, manufactured by Advantec Toyo Kaisha, Ltd.) to prepare a polytetrafluoroethylene resin particle dispersion (coating solution for the protective layer). [Chemical formula] [Chemical formula] <了
[0159] The protective coating solution was applied to the charge transport layer 1 by immersion to form a coating film, and the resulting coating film was dried at 40°C for 5 minutes. After drying, the coating film was irradiated with an electron beam for 1.6 seconds under conditions of an accelerating voltage of 70kV and an absorbed dose of 15kGy in a nitrogen atmosphere. Subsequently, the coating film was heat-treated for 15 seconds under conditions of a nitrogen atmosphere to reach a temperature of 135°C. The oxygen concentration from electron beam irradiation to the 15-second heat treatment was 15ppm. Next, the coating film was allowed to cool naturally in air until its temperature reached 25°C, and then heat-treated for 1 hour to reach a temperature of 105°C to form a surface layer (protective layer) with a thickness of 5.5μm. In this way, an electrophotographic photoreceptor having a support and a surface layer before surface polishing was fabricated.
[0160] <Surface treatment of electrophotographic photoreceptors> (Polishing of the electrophotographic photoreceptor before surface polishing) The surface of the electrophotographic photoreceptor was polished before surface shaping was formed. Polishing was performed using the polishing apparatus shown in Figure 2 under the following conditions. Abrasive sheet feed speed: 400 mm / min Rotation speed of the electrophotographic photoreceptor: 450 rpm Pressing the electrophotographic photoreceptor onto the backup roller; 3.5 mm Rotation direction of the polishing sheet and electrophotographic photoreceptor; with Backup roller; outer diameter 100mm, Asker C hardness 25 Polishing sheet A, which is attached to the polishing device, was made by mixing the abrasive grains used in GC3000 and GC2000, manufactured by Riken Corundum Co., Ltd. GC3000 (Abrasive sheet surface roughness Ra0.83μm) GC2000 (Abrasive sheet surface roughness Ra1.45μm) Abrasive sheet A (Surface roughness of abrasive sheet Ra 1.12 μm) The polishing time using polishing sheet A was set to 20 seconds.
[0161] (Measurement of polishing depth L (μm)) The maximum height Rmax of the electrophotographic photoreceptor after polishing was measured according to JIS B 0601 1982 using a surface roughness measuring instrument, SurfCorder SE3500, manufactured by Kosaka Laboratory Co., Ltd. The measurement conditions were set as follows. Measurements were taken at three arbitrary locations within a 5 mm square area, and the average value was adopted as the polishing depth L (μm). The polishing depth L of the electrophotographic photoreceptor after surface polishing was 0.75 μm. Furthermore, in Examples 1-2 to 1-25 described later, the polishing depth L of the electrophotographic photoreceptors that underwent surface processing was all 0.75 μm. (Measurement conditions) Pixel: R2μm Stylus: 0.7mN diamond needle Filter: 2CR Cutoff value: 0.08mm Measurement length: 2.5mm Feed speed: 0.1mm
[0162] [Examples 1-2 to 1-12, 1-21 to 1-26, Comparative Examples 1-1 to 1-3] An electrophotographic photoreceptor was prepared in the same manner as in Example 1-1, except that graft copolymer 1 was changed to the graft copolymer shown in Table 5 during the formation of the protective layer.
[0163] [Examples 1-13 to 1-14, 1-19 to 1-20] An electrophotographic photoreceptor was prepared in the same manner as in Example 1-1, except that the amount of graft copolymer 1 used in the formation of the protective layer was changed to parts by mass as shown in Table 5.
[0164] [Examples 1-15 to 1-18] An electrophotographic photoreceptor was fabricated in the same manner as in Example 1-1, except that the polytetrafluoroethylene resin particles used in forming the protective layer were changed to those having the average primary particle size and average roundness shown in Table 5.
[0165] [Examples 1-27] An electrophotographic photoreceptor was prepared in the same manner as in Example 1-1, except that the protective layer coating solution was prepared under the following conditions. 80 parts of tetrahydrofuran as a solvent was dissolved with 2.2 parts of graft copolymer 1 to prepare a dispersant solution. 31 parts of polytetrafluoroethylene resin particles (average primary particle size 210 nm, average circularity 0.85) were added to the obtained dispersant solution. Then, it was passed through a high-pressure homogenizer (trade name: Microfluidizer M-110EH, manufactured by Microfluidics Co., Ltd., USA) to obtain a polytetrafluoroethylene resin particle dispersion.
[0166] Subsequently, the following materials were prepared. · 161 parts of the charge transporting compound represented by the above formula C-26 · 5 parts of the guanamine compound represented by the following formula (L) · 2.6 parts of 3,5-di-t-butyl-4-hydroxytoluene (BHT) · 0.4 parts of dodecylbenzenesulfonic acid · 130 parts of cyclopentanone · 90 parts of cyclopentanol These were added to the polytetrafluoroethylene resin particle dispersion obtained above. Then, filtration was performed using a fluororesin filter (trade name: PF-040, manufactured by Advantec Toyo Co., Ltd.) to obtain a coating solution for the protective layer according to Example 1-27.
Chemical formula
[0167] 〔Example 1-28〕 In the formation of the surface layer, an electrophotographic photoreceptor was produced in the same manner as in Example 1-27, except that the guanamine compound represented by the above formula (L) was changed to a melamine compound represented by the following formula (M).
Chemical formula
[0168]
Table 5
[0169] <Evaluation of electrophotographic photoconductors> The electrophotographic photoreceptors obtained in Examples 1-1 to 1-28 and Comparative Examples 1-1 to 1-3 were evaluated as follows.
[0170] [Evaluation device 1-1] The electrophotographic photoconductor was installed in a Canon imagePRESS C800 copier (product name) and evaluated. Specifically, the evaluation apparatus was set up in an environment with a temperature of 23°C and a relative humidity of 50%RH. The fabricated electrophotographic photoreceptor was mounted onto a magenta process cartridge, which was then placed in the magenta process cartridge station for evaluation.
[0171] [Evaluation device 1-2] The electrophotographic photoreceptor was evaluated by mounting it in a modified Canon imagePRESS C800 (product name) copier. The charging means of the modified machine is a method of applying a voltage obtained by superimposing an AC voltage on a DC voltage to a roller-type contact charging member (charging roller), and the exposure means is a laser image exposure method (wavelength 680 nm). Specifically, the evaluation apparatus was set up in an environment with a temperature of 23°C and a relative humidity of 50%RH. The fabricated electrophotographic photoreceptor was mounted onto a magenta process cartridge, which was then placed in the magenta process cartridge station for evaluation. The charging conditions were adjusted so that the charging potential was -800V and the exposure potential was -300V, by adjusting the charging potential and the exposure amount of the exposure means. The surface potential of the electrophotographic photoreceptor was measured by removing the developing cartridge from the evaluation apparatus described above, inserting a potential measuring device into its place, and then measuring the potential. The potential measuring device consists of a potential measuring probe (product name: model6000B-8, manufactured by Trek Japan Co., Ltd.) placed at the developing position of the developing cartridge. The position of the potential measuring probe relative to the electrophotographic photoreceptor was set to the center in the direction of the electrograph line of the electrophotographic photoreceptor, with a gap of 3 mm from the surface of the electrophotographic photoreceptor. Furthermore, the potential of the central part of the electrophotographic photoreceptor was measured using a surface potential meter (product name: model344, manufactured by Trek Japan Co., Ltd.).
[0172] (Initial image evaluation) Image evaluation was performed using the evaluation apparatus 1-1 described above. Using A4 size gloss paper, a completely white image was output, and the number of image defects due to dispersion defects, i.e., black dots, contained in the area of one circumference of the electrophotographic photoreceptor in the output image was visually evaluated. The number of black dots with a diameter of 0.3 mm or more was evaluated. The area of one circumference of the electrophotographic photoreceptor is a rectangular area with a vertical dimension of 297 mm (the length of the long side of the A4 paper) and a horizontal dimension of 96.1 mm (the circumference of one circumference of the electrophotographic photoreceptor). In this disclosure, a smaller number of black dots is better, and the effects of this disclosure are achieved. The results of this evaluation are shown in Table 6.
[0173] (Evaluation of potential fluctuations during repeated use) The potential fluctuations during repeated use were evaluated using the evaluation apparatus 1-2 described above. A cartridge equipped with an electrophotographic photoreceptor was attached to the evaluation apparatus, and the photoreceptor was repeatedly used by passing 10,000 sheets of paper through it. At the station where the electrophotographic photoreceptor was installed, 10,000 images were repeatedly formed on A4 size plain paper for a single-color character image with a print density of 1%. The initial bright area potential at this time was compared with the bright area potential after 10,000 repeated image formations, and the difference between these two was defined as the potential fluctuation value (ΔVl). After 10,000 sheets were fed through, the paper was left for 5 minutes, the developing cartridge was replaced with a potential measuring device, and the bright area potential (Vlb) after repeated use was measured. The difference between the bright area potential after repeated use and the initial bright area potential (Vla) was defined as the bright area potential fluctuation amount (ΔVl = |Vlb| - |Vla|). In the evaluation using evaluation device 1-2, the bright area potential fluctuation amount was further measured after 100,000, 300,000, and 500,000 repeated uses. In this disclosure, the smaller the fluctuation in the bright area potential, the better, and the effects of this disclosure are achieved. The results of this evaluation are shown in Table 6.
[0174] [Table 6]
[0175] [Example 2-1] (Support 2) As the support (conductive support), a cylindrical aluminum cylinder (JIS-A3003, aluminum alloy, outer diameter 30 mm, length 357.5 mm, wall thickness 0.7 mm) was machined and used. Ultrasonic cleaning was performed in a cleaning solution containing detergent (product name: Chemicol CT, manufactured by Tokiwa Chemical Co., Ltd.) in pure water, followed by rinsing off the cleaning solution, and then further ultrasonic cleaning in pure water to degrease it, which was then used as support 2.
[0176] (Bottom layer 2) Zinc oxide particles (average particle size: 70 nm, specific surface area: 15 m²) 2 60 parts of ( / g) were mixed with 500 parts of tetrahydrofuran by stirring. 0.75 parts of a silane coupling agent (compound name: N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, trade name: KBM603, manufactured by Shin-Etsu Chemical Co., Ltd.) were added to the resulting mixture and stirred for 2 hours. Then, the tetrahydrofuran was removed by distillation under reduced pressure, and the mixture was heated and dried at 120°C for 3 hours to obtain surface-treated zinc oxide particles.
[0177] Next, 25 parts of butyral (product name: BM-1, manufactured by Sekisui Chemical Co., Ltd.) and 22.5 parts of blocked isocyanate (product name: Sumijool BL-3173, manufactured by Sumitomo Bayern Urethanes) were dissolved in 142 parts of methyl ethyl ketone. To this solution, 100 parts of the surface-treated zinc oxide particles and 1 part of anthraquinone were added, and the mixture was dispersed for 5 hours using glass beads with a diameter of 1 mm in a sand mill. After dispersion treatment, 0.008 parts of dioctyltin dilaurate and 6.5 parts of silicone resin particles (Tospar 145, manufactured by GE Toshiba Silicone Co., Ltd.) were added and stirred to prepare a coating solution for the undercoat layer. The obtained undercoating solution was applied to the support 2 by immersion to form a coating film, and the coating film was dried at 190°C for 24 minutes to form an undercoating layer 2 with a thickness of 15 μm.
[0178] (Charge generation layer 2) Next, I prepared the following materials. 15 parts of chlorogallium phthalocyanine crystals having strong diffraction peaks at at least 7.4°, 16.6°, 25.5°, and 28.3° of the Bragg angle (2θ±0.2°) for CuKα characteristic X-rays. • 10 parts of vinyl chloride-vinyl acetate copolymer resin (VMCH, manufactured by Union Carbide Japan Co., Ltd.) 300 parts of n-butyl alcohol These were mixed and dispersed for 4 hours using a sand mill with 1 mm diameter glass beads to prepare a coating solution for the charge generation layer. This charge generation layer coating solution was applied to the undercoat layer 2 by immersion, and the resulting coating film was dried at 150°C for 5 minutes to form a charge generation layer 2 with a thickness of 0.18 μm.
[0179] (Charge transport layer 2) Next, 10 parts of polytetrafluoroethylene resin particles (average primary particle size 210 nm, average roundness 0.85), 0.50 parts of the aforementioned graft copolymer 1, and 24 parts of tetrahydrofuran were stirred and mixed for 48 hours while maintaining a liquid temperature of 20°C to obtain preparation A. Next, I prepared the following materials. • N,N'-bis(3-methylphenyl)-N,N'-diphenylbenzicine 53.2 parts • Bisphenol Z-type polycarbonate resin (viscosity-average molecular weight 40,000) 14.1 parts • 0.26 parts of 2,6-di-t-butyl-4-methylphenol as an antioxidant. These were mixed together, and 250 parts of tetrahydrofuran were added and dissolved to obtain preparation B. After adding preparation A to preparation B and stirring, the mixture was passed through a high-pressure disperser (product name: Microfluidizer M-110EH, manufactured by Microfluidics, Inc., USA) to obtain a dispersion. Subsequently, fluorine-modified silicone oil (product name: FL-100, manufactured by Shin-Etsu Silicone Co., Ltd.) was added to the dispersion to a concentration of 5 ppm, and the mixture was filtered using a polyflon filter (product name: PF-040, manufactured by Advantec Toyo Co., Ltd.) to prepare a coating solution for the charge transport layer. This charge transport layer coating solution was applied to the charge generating layer 2 by immersion to form a coating film, and the resulting coating film was dried at 150°C for 25 minutes to form a charge transport layer 2 with a thickness of 30 μm. In this way, an electrophotographic photoreceptor was fabricated.
[0180] [Examples 2-2 to 2-12, 2-21 to 2-26, Comparative Examples 2-1 to 2-3] An electrophotographic photoreceptor was prepared in the same manner as in Example 2-1, except that graft copolymer 1 was changed to the graft copolymer shown in Table 7 during the formation of the protective layer.
[0181] [Examples 2-13 to 2-14, 2-19 to 2-20] An electrophotographic photoreceptor was prepared in the same manner as in Example 2-1, except that the amount of graft copolymer 1 used in the formation of the protective layer was changed to parts by mass as shown in Table 7.
[0182] [Examples 2-15 to 2-18] An electrophotographic photoreceptor was fabricated in the same manner as in Example 2-1, except that the polytetrafluoroethylene resin particles used in forming the protective layer were changed to those having the average primary particle size and average roundness shown in Table 7.
[0183] [Table 7]
[0184] <Evaluation of electrophotographic photoconductors> The electrophotographic photoreceptors obtained in Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-3 were evaluated as follows.
[0185] [Evaluation device 2-1] The electrophotographic photoconductor was installed in a Canon imageRUNNER iR-ADV C5051 copier and evaluated. Specifically, the evaluation apparatus was set up in an environment with a temperature of 23°C and a relative humidity of 50%RH. The fabricated electrophotographic photoreceptor was mounted on a cyan process cartridge, and the cartridge was then placed in the cyan process cartridge station for evaluation.
[0186] [Evaluation device 2-2] The electrophotographic photoreceptor was installed in a modified Canon imageRUNNER iR-ADV C5051 copier (the charging method involves applying a voltage obtained by superimposing an AC voltage on a DC voltage to a roller-type contact charging element (charging roller), and the exposure method is a laser image exposure method (wavelength 780nm)) and evaluated. For further details, the evaluation apparatus was set up in an environment with a temperature of 23°C and a relative humidity of 50%RH. The fabricated electrophotographic photoreceptor was mounted on a cyan process cartridge, and then the cartridge was placed in the cyan process cartridge station for evaluation. The charging conditions were adjusted so that the charging potential was -700V and the exposure potential was -200V, by adjusting the charging potential and the exposure amount of the exposure means. The surface potential of the electrophotographic photoreceptor was measured by removing the developing cartridge from the evaluation apparatus described above, inserting a potential measuring device into its place, and then measuring the potential. The potential measuring device consists of a potential measuring probe (product name: model6000B-8, manufactured by Trek Japan Co., Ltd.) placed at the developing position of the developing cartridge. The position of the potential measuring probe relative to the electrophotographic photoreceptor was set to the center in the direction of the electrograph line of the electrophotographic photoreceptor, with a gap of 3 mm from the surface of the electrophotographic photoreceptor. Furthermore, the potential of the central part of the electrophotographic photoreceptor was measured using a surface potential meter (product name: model344, manufactured by Trek Japan Co., Ltd.).
[0187] (Initial image evaluation) Image evaluation was performed using the evaluation apparatus 2-1 described above. Using A4 size gloss paper, a completely white image was output, and the number of image defects due to dispersion defects, i.e., black dots, contained in the area of one circumference of the electrophotographic photoreceptor in the output image was visually evaluated. The number of black dots with a diameter of 0.3 mm or more was evaluated. The area of one circumference of the electrophotographic photoreceptor is a rectangular area with a vertical dimension of 297 mm (the length of the long side of the A4 paper) and a horizontal dimension of 94.2 mm (the circumference of one circumference of the electrophotographic photoreceptor). In this disclosure, a smaller number of black dots is better, and the effects of this disclosure are achieved. The results of this evaluation are shown in Table 8.
[0188] (Evaluation of potential fluctuations during repeated use) The potential fluctuation evaluation during repeated use was performed using the evaluation device 2-2 described above. A cartridge equipped with an electrophotographic photoreceptor was attached to the evaluation device, and the photoreceptor was repeatedly used by passing 50,000 sheets of paper through it. At the station where the electrophotographic photoreceptor was installed, a monochrome character image with a print density of 1% was repeatedly formed on A4 size plain paper for 50,000 images. The initial bright area potential at this time and the bright area potential after 50,000 repeated image formations were compared, and this was defined as the potential fluctuation value (ΔVl). The difference between the bright area potential after repeated use and the initial bright area potential (Vla) was defined as the bright area potential fluctuation amount (ΔVl = |Vlb| - |Vla|). In the evaluation using evaluation device 1-2, the bright area potential fluctuation amount during an additional 500,000 repeated uses was measured. In this disclosure, the smaller the fluctuation in the bright area potential, the better, and the effects of this disclosure are achieved. The results of this evaluation are shown in Table 8.
[0189] [Table 8] [Explanation of Symbols]
[0190] 101 Support 102 Lower layer 103 Charge generation layer 104 Charge transport layer 105 Surface layer 1. Electrophotographic photoreceptor 2. Charging means 3 Exposure light 4. Developing means 5. Transfer means 6 Transfer material 7. Pre-exposure light 8. Cleaning methods 9 Process Cartridges 10 Intermediate Transfer 11 Transfer paper 12 Paper feed path 13 Paper feed tray 14. Secondary transfer means 15 Fixing means 16 Paper output section 17 Process cartridge for yellow color 18 Magenta Process Cartridges 19 Cyan process cartridge 20 Process cartridges for black color
Claims
1. An electrophotographic photoreceptor having a surface layer, The surface layer is Fluorine atom-containing resin particles; A binding material; A polymer A having a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), Contains 1. An electrophotographic photoreceptor comprising: 【Chemistry 1】 (In formula (1), R 11 represents a hydrogen atom or a methyl group, R 12 represents a single bond, a methylene group, or an ethylene group, n is an integer of 3 or more, n Rf 1 each independently represents a perfluoroalkylene group having 1 to 5 carbon atoms or a perfluoroalkylidene group having 1 to 5 carbon atoms, Rf 2 represents a perfluoroalkyl group having 1 to 5 carbon atoms. 【Chemistry 2】 (In formula (2), Y A1 represents an unsubstituted alkylene group; Y B represents an unsubstituted alkylene group, an alkylene group substituted with a halogen atom, an alkylene group substituted with a hydroxyl group, an ester bond (--COO--), an amide bond (--NHCO--), a urethane bond (--NHCOO--), or a divalent linking group derived by combining one or more selected from these groups and bonds with -O- or -S-, or a single bond; Z A represents a structure represented by the following formula (2A), a cyano group, or a phenyl group: R 21 and R 22 each independently represent a hydrogen atom or a methyl group; m is an integer between 25 and 150. 【Chemistry 3】 (In formula (2A), Z A1 represents an alkyl group having 1 to 4 carbon atoms.)
2. The n Rf in the formula (1) 1 are each independently a perfluoroalkylene group having 1 to 3 carbon atoms or a perfluoroalkylidene group having 1 to 3 carbon atoms, 2 2. The electrophotographic photoreceptor according to claim 1, wherein is a perfluoroalkyl group having 1 to 3 carbon atoms.
3. In the formula (1), n Rf 1 , and Rf 2 3. The electrophotographic photoreceptor according to claim 1, wherein the total number of carbon atoms in the groups is 6 or more and 9 or less.
4. 4. The electrophotographic photoreceptor according to claim 1, wherein the weight average molecular weight of the polymer A is 16,000 or more and 100,000 or less.
5. The electrophotographic photoreceptor according to any one of claims 1 to 4, wherein the content of the polymer A in the surface layer is 2% by mass to 10% by mass with respect to the content of the fluorine atom-containing resin particles in the surface layer.
6. The electrophotographic photoreceptor according to any one of claims 1 to 5, wherein the polymer A has, as structural units, only the structural unit represented by the formula (1) and the structural unit represented by the formula (2).
7. 7. The electrophotographic photoreceptor according to claim 1, wherein the fluorine atom-containing resin particles are polytetrafluoroethylene resin particles.
8. 8. The electrophotographic photoreceptor according to claim 1, wherein the arithmetic average of the major axis of the primary particles of the fluorine-containing resin particles is 150 nm or more and 300 nm or less.
9. 9. The electrophotographic photoreceptor according to claim 1, wherein the content of the fluorine atom-containing resin particles in the surface layer is from 5% by mass to 40% by mass with respect to the total mass of the surface layer.
10. 10. The electrophotographic photoreceptor according to claim 1, wherein the binder material comprises a cured product of a hole transporting compound having a polymerizable functional group.
11. The hole transporting compound having a polymerizable functional group is at least one compound selected from the group consisting of a compound represented by the following formula (CT-1) and a compound represented by the following formula (CT-2): The electrophotographic photoreceptor according to claim 10. 【Chemistry 4】 (In formula (CT-1), Ar 11 ~Ar 13 each independently represents an aryl group which may have a substituent, and the substituent which the aryl group may have is an alkyl group having from 1 to 6 carbon atoms, and a monovalent functional group represented by any one of the following formulae (P-1) to (P-3), with the proviso that the compound represented by formula (CT-1) has at least one aryl group having, as a substituent, a monovalent functional group represented by any one of the following formulae (P-1) to (P-3). 【Chemistry 5】 (In formula (CT-2), Ar 21 ~Ar 24 each independently represents an aryl group which may have a substituent, and the substituent which the aryl group may have is an alkyl group having from 1 to 6 carbon atoms, or a monovalent functional group represented by any one of the following formulae (P-1) to (P-3): Ar 25 represents an arylene group which may have a substituent, and the substituent which the arylene group may have is an alkyl group having from 1 to 6 carbon atoms, and a monovalent functional group represented by any one of the following formulas (P-1) to (P-3), with the proviso that the compound represented by formula (CT-2) has at least one group selected from an aryl group having as a substituent a monovalent functional group represented by any one of the following formulas (P-1) to (P-3), and an arylene group having as a substituent a monovalent functional group represented by any one of the following formulas (P-1) to (P-3). 【Chemistry 6】 (In formula (P-1), Z 11 represents a single bond or an alkylene group having 1 to 6 carbon atoms; X 11 represents a hydrogen atom or a methyl group.) 【Chemistry 7】 (In formula (P-2), Z 21 represents a single bond or an alkylene group having 1 to 6 carbon atoms. 【Chemistry 8】 (In formula (P-3), Z 31 represents a single bond or an alkylene group having 1 to 6 carbon atoms.
12. 12. The electrophotographic photoreceptor according to claim 10, wherein the content of the fluorine atom-containing resin particles in the surface layer is from 5% by mass to 40% by mass with respect to the total mass of the surface layer.
13. The electrophotographic photoreceptor according to any one of claims 1 to 9, wherein the binder material comprises a cured product of a charge transporting compound and at least one triazine compound selected from a guanamine compound and a melamine compound.
14. The electrophotographic photoreceptor according to claim 13, wherein the charge transporting compound has at least one polymerizable functional group selected from a methylol group and a methoxy group.
15. 15. The electrophotographic photoreceptor according to claim 13, wherein the content of the fluorine atom-containing resin particles in the surface layer is from 5% by mass to 15% by mass with respect to the total mass of the surface layer.
16. The binder material includes a thermoplastic resin, the surface layer further contains a charge transport material, The thermoplastic resin is at least one resin selected from a polycarbonate resin and a polyarylate resin. The electrophotographic photoreceptor according to any one of claims 1 to 9.
17. 17. The electrophotographic photoreceptor according to claim 16, wherein the charge transport material is at least one compound selected from the group consisting of compounds represented by the following formula (4) and compounds represented by the following formula (5): 【Chemistry 9】 (In formula (4), R C21 , R C22 , and R C23 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms; C21 , two R C22 , and two R C23 may be the same as or different from each other.) 【Chemistry 10】 (In formula (5), R C11 , R C12 , R C13 , R C14 , R C15 , and R C16 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an aryl group having 6 to 30 carbon atoms, or two adjacent substituents are bonded to each other to form a hydrocarbon ring structure. m and n each independently represent 0, 1, or 2.
18. 18. The electrophotographic photoreceptor according to claim 16, wherein a content of the fluorine atom-containing resin particles in the surface layer is from 5% by mass to 15% by mass with respect to a total mass of the surface layer.
19. 19. A process cartridge which integrally supports the electrophotographic photosensitive member according to any one of claims 1 to 18 and at least one means selected from the group consisting of a charging means, a developing means, and a cleaning means, and is detachably mountable to a main body of an electrophotographic apparatus.
20. 19. An electrophotographic apparatus comprising the electrophotographic photoreceptor according to claim 1, a charging unit, an exposing unit, a developing unit, and a transferring unit.
21. A method for producing an electrophotographic photoreceptor having a surface layer, comprising the steps of: The manufacturing method comprises: A polymer A having a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), Fluorine atom-containing resin particles; At least one selected from a binding material and a raw material for a binding material; A step of preparing a coating liquid for a surface layer comprising the steps of: forming a coating film of the coating liquid for the surface layer, and subjecting the coating film to at least one treatment selected from drying and curing, thereby forming the surface layer; having 2. A method for producing an electrophotographic photoreceptor comprising the steps of: 【Chemistry 11】 (In formula (1), R 11 represents a hydrogen atom or a methyl group, R 12 represents a single bond, a methylene group, or an ethylene group, n is an integer of 3 or more, n Rf 1 each independently represents a perfluoroalkylene group having 1 to 5 carbon atoms, or a perfluoroalkylidene group having 1 to 5 carbon atoms, Rf 2 represents a perfluoroalkyl group having 1 to 5 carbon atoms. 【Chemistry 12】 (In formula (2), Y A1 represents an unsubstituted alkylene group; Y B represents an unsubstituted alkylene group, an alkylene group substituted with a halogen atom, an alkylene group substituted with a hydroxyl group, an ester bond (--COO--), an amide bond (--NHCO--), a urethane bond (--NHCOO--), or a divalent linking group derived by combining one or more selected from these groups and bonds with -O- or -S-, or a single bond; Z A represents a structure represented by the following formula (2A), a cyano group, or a phenyl group: R 21 and R 22 each independently represent a hydrogen atom or a methyl group; m is an integer between 25 and 150. 【Chemistry 13】 (In formula (2A), Z A1 represents an alkyl group having 1 to 4 carbon atoms.)